Comparing fattening characteristics of sheep breeds with different genotypes - Bokor, Beáta; Abayné Hamar, Enikő; Tóth, Gábor; Tőzsér, János; Pajor, Ferenc; Póti, Péter (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
In this study we examined male lambs of three breeds (Hungarian Merino, German Mutton Merino, German Blackheaded Mutton) during an intensive fattening with complete feed mixture. We analysed lamb growth, fattening results and parameters of meat turnout and quality based on slaughterhouse data.According to our research the weaning weight of meat type lambs significanty differed from the average weaning weight of Hungarian Merino lambs (20,28 kg). German Blackheaded Mutton lambs showed outstanding average daily weight gain (381 g/day). Among the examined breeds German Blackheaded Mutton lambs showed greater intensity of growth than the Hungarian Merino. The To sum up, our findings reveal that in case of intensive housing and feeding conditions Hungarian Merino results approach German Mutton Merino fattening index.
Keywords: fattening; growth rate; merino; environmental conditions